Leveraging STARA competencies and green creativity to boost green organisational innovative evidence: A praxis for sustainable development. (17th February 2021) - Ogbeibu, Samuel; Jabbour, Charbel Jose Chiappetta; Gaskin, James; Senadjki, Abdelhak; Hughes, Mathew
Abstract: Radical technological advancements and the relentless progression of climate change compel organisations to ensure their workforce consistently exercise their creativity toward innovative green initiatives. These endeavours are essential to achieve the United Nations' (UN) sustainable development goals (SDGs). To do so, organisations require competencies fundamental to smart technologies, artificial intelligence, robotics and algorithms (STARA). STARA competencies are relevant for leaders to bolster green organisational innovative evidence (GOIE). GOIE can help to attract potential investors keen on advancing the UN's SDG agenda on environmental sustainability. However, eclipsed by a volatile environment, and despite the green innovation potential of several manufacturing organisations, investors are reluctant to invest and commit funds without evidence of green innovation. We therefore, investigate how leader STARA competence (LSC), green creativity components (task motivation, creativity skills and expertise) and environmental dynamism can aid organisations to boost their GOIE. Our key findings are as follows: (a) though green task motivation shows a stronger association with green creativity skills, LSC has a large influence on green creativity skills; (b) green creativity skills exert a strong influence on GOIE while also playing a competitive and complimentary mediating role in our model and (c) environmental dynamism is negatively associated with green creativity skills and GOIE. Furthermore, to validate indirect ( v ) effects size in mediation analysis, we propose a new and more approachable benchmark for v effect size estimations. Organisational and environmental policy implications are discussed.